2023
DOI: 10.20524/aog.2023.0777
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of endoscopic submucosal dissection for the treatment of superficial gastric neoplasms in non-Asian countries: a systematic review and meta-analysis

Abstract: Background Endoscopic submucosal dissection (ESD) is now considered the standard treatment for early gastric cancer (EGC). However, the widespread adoption of ESD in western countries has been slow. We performed a systematic review to evaluate short-term outcomes of ESD for EGC in non-Asian countries. Methods We searched 3 electronic databases from inception until October 26, 2022. Primary outcomes were en bloc , R0 and curative resections rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Delayed postoperative bleeding is the most common complication induced by ESD. Benites-Goñi et al reported that delayed postoperative bleeding occurred in 5-7% of patients who underwent ESD [35]. Of the nine RCTs included in our meta-analysis, the rate of delayed postoperative bleeding in the vonoprazan group ranged from 0 to 5.4%.…”
Section: Discussionmentioning
confidence: 78%
“…Delayed postoperative bleeding is the most common complication induced by ESD. Benites-Goñi et al reported that delayed postoperative bleeding occurred in 5-7% of patients who underwent ESD [35]. Of the nine RCTs included in our meta-analysis, the rate of delayed postoperative bleeding in the vonoprazan group ranged from 0 to 5.4%.…”
Section: Discussionmentioning
confidence: 78%
“…found that patients with well‐differentiated lesions sized <3 cm, lesions showing a submucosal invasion depth of <500 μm, and undifferentiated lesions sized <2 cm confined to the mucosa were almost entirely free of lymph node metastasis. Such lesions were included in the absolute indications or expanded indications for endoscopic resection 2–5 . The invasion depth of early gastric cancer is currently determined using traditional and ultrasound endoscopy 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Such lesions were included in the absolute indications or expanded indications for endoscopic resection. 2 , 3 , 4 , 5 The invasion depth of early gastric cancer is currently determined using traditional and ultrasound endoscopy. 6 , 7 , 8 The results of traditional and ultrasound endoscopy did not meet the needs of endoscopic submucosal dissection.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the recently published systematic review by Benites-Goñi et al on the short-term outcomes of endoscopic submucosal dissection for the treatment of superficial gastric neoplasms in non-Asian countries [ 1 ]. Regrettably, we noted that our previous study published in 2020, indexed in PubMed with full open access, was not included in the analysis.…”
mentioning
confidence: 99%
“…Therefore, the estimates reported in this systematic review could have been different if the data from our study had also been considered. We would suggest that the authors should carry out a further check of the accuracy in the literature review they performed on October 26, 2022 [ 1 ].…”
mentioning
confidence: 99%